MENINGKATKAN KETERAMPILAN PROSES SAINS MAHASISWA MELALUI PENGEMBANGAN PROGRAM PEMBELAJARAN FISIKA MENGGUNAKAN MODEL INKUIRI - Verawati, Ni Nyoman Sri Putu (Lensa : Jurnal Kependidikan Fisika, 2013)
This study aimed to improve science process skills of students in learning physics through program using the inquiry learning model. This research is action research through the stages of planning, implementation, observation, and reflection, its are implemented in cyclical form. The subjects were students of biology education courses that take the course Physics I in the first semester of academic year 2013/2014. The instrument in this study using the Performance Appraisal Sheet Process (PASP) based on woorksheet to obtain data of science process skills of students. The results showed that as many as 75 % of students have a science process skills with good category, 17 % of students with unfavorable category, 8 % of students categorized as very poor (bad). As for each component of science process skills, students appear to difficulties in conducting data analysis with a score of 59,8 but both in carrying out experiments with a score of 70,5. From the research that has been done can be concluded that the learning program using the inquiry model in physics learning can improve student science process skills.